The Linguistic-Mental Synonymy - Tonoyan, Tadevos (Bulletin of Yerevan University B: Philology, 2025)
In this article, an attempt was made to introduce a new term into the field of linguistics: linguo-mental synonymy. It was methodically shown that the need for this new term began to be felt during the study of the texts created in the domain of the same language. The texts created in Armenian served as material for this, the vitality and high value of which was proved by their connection with the collective memory of the people. Texts created both in Armenian and in other languages ​​are a reflection of linguistic value systems of the communities and peoples who speak those languages, and these texts are connected to each other by internal ties, especially by the generality of value system realities. One of the important starting points of the article was to prove that generality. Undoubtedly, posing such a problem logically leads to the fact that there is a need to correct and complete the already existing understandings of some ideas and realities in linguistics, and ultimately also the understanding of terms. We faced such a problem when it was necessary to clarify the ideas about the context. A similar demand also arose regarding the principles of classification of individual texts.We tried to find the semantic commonality between symbols or words with symbolic meaning appearing in the texts. This led us to record the phenomenon of linguo-mental synonymy.
Keywords: synonymy; linguistic synonymy; speech; text; context